2003
DOI: 10.1016/s0006-3495(03)70039-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements of the Fructan-Lipid Interaction

Abstract: Fructans are a group of fructose-based oligo- and polysaccharides. They are proposed to be involved in membrane protection of plants during dehydration. In accordance with this hypothesis, they show an interaction with hydrated lipid model systems. However, the structural requirements for this interaction are not known both with respect to the fructans as to the lipids. To get insight into this matter, the interaction of several inulins and levan with lipids was investigated using a monomolecular lipid system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 34 publications
2
54
0
3
Order By: Relevance
“…Inulin‐type fructans are not commonly used as cryoprotectants, despite being known as water‐soluble natural cryoprotective agents synthesized by many plant, fungi and bacteria (Hubalek, 2003). Fructans directly interact with lipids of biological membranes and stabilize them under cold as well as dry conditions (Demel et al ., 1998; Vereyken et al ., 2003). Inulin can also serve as a fermentation substrate, as several F. prausnitzii strains can use inulin (Duncan et al ., 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Inulin‐type fructans are not commonly used as cryoprotectants, despite being known as water‐soluble natural cryoprotective agents synthesized by many plant, fungi and bacteria (Hubalek, 2003). Fructans directly interact with lipids of biological membranes and stabilize them under cold as well as dry conditions (Demel et al ., 1998; Vereyken et al ., 2003). Inulin can also serve as a fermentation substrate, as several F. prausnitzii strains can use inulin (Duncan et al ., 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [26][27][28] have indicated that inulintype FOSs are very flexible and may form lefthanded or right-handed helical structures. In contrast, levan-type FOSs are relatively rigid, with a preference for left-handed helix formation.…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly long-chain structure of inulins ensure long fermentation times in the colon. Inulin chain length dependence interactions with glycolipids and phospholipids have been reported in model membrane systems (Vereyken, Kuik, Evers, Rijken, & Kruijff, 2003). As the degree of polymerization increased, residual fructo-oligosaccharides increased after growth of the bifidobacteria strains and the rate of consumption of fructo-oligosaccharides decreased (Perrin et al, 2002).…”
Section: Introductionmentioning
confidence: 92%